2018
DOI: 10.3390/cancers10120524
|View full text |Cite
|
Sign up to set email alerts
|

BRCA Mutations and Breast Cancer Prevention

Abstract: Women who inherit a deleterious BRCA1 or BRCA2 mutation face substantially increased risks of developing breast cancer, which is estimated at 70%. Although annual screening with magnetic resonance imaging (MRI) and mammography promotes the earlier detection of the disease, the gold standard for the primary prevention of breast cancer remains bilateral mastectomy. In the current paper, I review the evidence regarding the management of healthy BRCA mutation carriers, including key risk factors and protective fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 119 publications
(157 reference statements)
3
67
0
2
Order By: Relevance
“…Besides, differences in ethnic background, recruitment criteria, and pathogenic mutation location may exert some effect. It was reported that the risk of breast cancer increased substantially between the ages of 30 and 50 years for BRCA1 carriers, while the risk was highest between the ages of 40 and 60 years for BRCA2 carriers, which was simulated to our results. Other aspects of basic characteristics of this study were favor of previous literatures …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Besides, differences in ethnic background, recruitment criteria, and pathogenic mutation location may exert some effect. It was reported that the risk of breast cancer increased substantially between the ages of 30 and 50 years for BRCA1 carriers, while the risk was highest between the ages of 40 and 60 years for BRCA2 carriers, which was simulated to our results. Other aspects of basic characteristics of this study were favor of previous literatures …”
Section: Discussionsupporting
confidence: 81%
“…Currently, apart from clinical breast examination, mammography, ultrasound, and breast magnetic resonance imaging, it is wide recognition that prophylactic removal of the ovaries and risk‐reducing bilateral mastectomy are the most effective prevention measures to BRCA ‐carriers and BRCA ‐associated breast cancers . Although the role of prophylactic oophorectomy is mixed in prior studies, it is suggested that prophylactic oophorectomy might not impact breast cancer incidence, but is associated with a favorable survival for this high‐risk population . Likewise, bilateral prophylactic mastectomy, sacrificing the quality of life, is regarded as one of the most effective measures to prevent BRCA ‐associated breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐funded MRI screening is offered to women aged 50 years or older. In addition, other options are discussed with the patient, including prophylactic surgeries, for example, bilateral mastectomy and risk‐reducing bilateral salpingo‐oophorectomy (after child bearing is completed), lifestyle recommendations (weight management, physical activity, diet, smoking, and alcohol intake), and, if eligible, risk‐reducing medication and clinical trials (eg, the BRCA‐D study)…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective review was performed using prospectively collected 15 and, if eligible, risk-reducing medication 16 and clinical trials (eg, the BRCA-D study). 17 For this study, de-identified data were extracted from the local…”
Section: Methodsmentioning
confidence: 99%